Interaction between Shiga Toxin and Monoclonal Antibodies: Binding Characteristics and in Vitro Neutralizing Abilities - Letícia B. Rocha (Toxins, 2012)
Monoclonal antibodies (MAbs) have been employed either for diagnosis or treatment of infections caused by different pathogens. Specifically for Shiga toxin-producing Escherichia coli (STEC), numerous immunoassays have been developed for STEC diagnosis, showing variability in sensitivity and specificity when evaluated by reference laboratories, and no therapy or vaccines are currently approved. Thus, the aim of this work was the characterization of the interaction between MAbs against Stx1 and Stx2 toxins and their neutralizing abilities to enable their use as tools for diagnosis and therapy. The selected clones designated 3E2 (anti-Stx1) and 2E11 (anti-Stx2) were classified as IgG1. 3E2 recognized the B subunit of Stx1 with an affinity constant of 2.5 × 10−10 M, detected as little as 6.2 ng of Stx1 and was stable up to 50 ºC. In contrast, 2E11 recognized the A subunit of Stx2, was stable up to 70 ºC, had a high dissociation constant of  6.1 × 10−10 M, and detected as little as 12.5 ng of Stx2. Neutralization tests showed that 160 ng of 3E2 MAb inhibited 80% of Stx1 activity and 500 µg 2E11 MAb were required for 60% inhibition of Stx2 activity. These MAb amounts reversed 25 to 80% of the cytotoxicity triggered by different STEC isolates. In conclusion, these MAbs show suitable characteristics for their use in STEC diagnosis and encourage future studies to investigate their protective efficacy.